Adverse and Positive Childhood Experiences and Emotional Regulation Difficulties in a Sample of Incarcerated Men - Bárbara Maia; Ana Rita Cruz; Olga Cunha (Behavioral Sciences, 2025)
Adverse childhood experiences (ACEs) are linked to a higher risk of criminal behaviour, while positive childhood experiences (PCEs) may offer a protective effect by mitigating the negative impact of ACEs. Both ACEs and PCEs play a significant role in shaping emotional regulation. However, research on the influence of PCEs within incarcerated populations remains limited. This study aimed to examine the associations between ACEs, PCEs, and emotional regulation difficulties in a prison sample, and to explore whether PCEs moderate the relationship between ACEs and emotional regulation difficulties in adulthood. The analysis considered both the overall emotional regulation difficulties score and its specific dimensions—strategies, non-acceptance, impulse, goals, awareness, and clarity. The study included 283 men, with a mean age of 40.03 (SD = 11.64), ranging from 19 to 84 years, who were incarcerated in seven prisons in northern Portugal. Data were collected using the Adverse Childhood Experiences Scale, the Benevolent Childhood Experiences Scale, and the Difficulties in Emotional Regulation Scale—Short Form. The results revealed statistically significant positive correlations between ACEs and overall emotional regulation difficulties, as well as with nearly all subscales (strategies, impulse, goals, awareness, and clarity). Conversely, PCEs were significantly negatively correlated with overall emotional regulation difficulties and most subscales (impulse, goals, awareness, and clarity). However, PCEs did not moderate the relationship between ACEs and emotional regulation difficulties. These findings may be influenced by the characteristics of the sample, highlighting the need for further research—preferably longitudinal studies—to better assess the potential moderating role of PCEs. Such research could enhance the effectiveness of prevention and intervention strategies for incarcerated populations.